PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DAN DAYA TARIK WISATAWAN MANCANEGARA - Titis Wisnu Wijaya (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
The quality enhancement of human resource is supporting program to increase tourist magnetismin Krapyak Wetan. This village has interesting tour i.e. nature tour and art. The people has notrealized that existing potency can increase the society economy. The quality enhancement of humanresource is one of the essential part in increasing magnetism tourist. Based on the observation,people are relying on the government. The government is focusing on tourism place, yet humanresource needs to be improved. Tourism growth is running fast in many places incurring domesticand foreign tourist. In line with the tourism competition and objectify Krapyak Wetan as foreign touristdestination, people needs to learn and to master English as an international language. In this case,community engagement program needs to be implemented in quality enhancement of humanresource through international language learning. The learning method is to give an English learningand practicing two times in a week for four months. In short-term, especially young people keens toapply the knowledge not only in their environment, but also in school. In long-term, people has beenlearning and mastering International language before foreign tourist visits to enjoy local tourism inKrapyak Wetan.